The Effect of Auditor Competence and Auditor Independence on Audit Quality with Professional Skepticism as a Moderating Variable - Mega Nasution; Mona Eftarina; Harti Budi Yanti (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to examine the effect of auditor competence, independence, and professionalism on audit quality, with evidence competence acting as a mediating variable. The research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to auditors working in public accounting firms. The research population comprises all auditors employed at public accounting firms located in the DKI Jakarta and Tangerang regions. Based on 2024 data, there are 187 public accounting firms with approximately 2,340 auditors. Using the Slovin formula with a 5% margin of error, a sample of 342 respondents was determined. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings indicate that audit quality is strongly influenced by auditor competence and independence, both of which have a positive and significant direct effect on audit quality, while professionalism does not show a significant direct effect. Furthermore, evidence competence plays a crucial mediating role by significantly strengthening the effects of competence, independence, and professionalism on audit quality